A new synthetic route for the synthesis of enantioenriched 1, 2, 3, 4-tetrahydronaphthalene-derived 1, 3-diols. Issue 22 (17th November 2018) - Cheng, Feng; Cai, Chen; Yang, Xing; Lin, Zi-Wei; Hu, Xiao-Song; Huang, Yi-Yong
Abstract: In this report, we presented a new approach to access a (1, 3-butadiene-2-yl)carbinol, (1 R, 2 R )- and (1 S, 2 S )-1-(hydroxymethyl)-1-vinyl-1, 2, 3, 4-tetrahydronaphthalene-2-ols. Starting from commercially available 1, 4-diol-2-butyne, a six-step synthesis involving dibromination, Zn-mediated addition reaction of phenylpropyl aldehyde, epoxidation, epoxy–arene cyclization, and resolution with D (+)-Camphor afforded the title compounds. Graphical Abstract: We herein presented a new approach to access a (1, 3-butandien-2-yl)carbinol, (1R, 2R)- and (1S, 2S)-1-(hydroxymethyl)-1-vinyl-1, 2, 3, 4-tetrahydronaphthalen-2-ols.